2021
DOI: 10.1371/journal.pone.0245970
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of magnetic resonance fingerprinting-based T1 mapping of the healthy prostate at 1.5 and 3.0 T: A proof-of-concept study

Abstract: Facilitating clinical translation of quantitative imaging techniques has been suggested as means of improving interobserver agreement and diagnostic accuracy of multiparametric magnetic resonance imaging (mpMRI) of the prostate. One such technique, magnetic resonance fingerprinting (MRF), has significant competitive advantages over conventional mapping techniques in terms of its multi-site reproducibility, short scanning time and inherent robustness to motion. It has also been shown to improve the detection of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…MRF has been shown to provide highly reproducible quantitative maps in both 2D 14 and 3D 15 acquisitions. MRF‐derived T 1 and T 2 measurements are also repeatable over time, 16 with excellent reproducibility in vivo across different scanner types 17,18 . Several in vivo multicenter studies demonstrated high levels of repeatability and reproducibility of MRF in the brain 17,19 .…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…MRF has been shown to provide highly reproducible quantitative maps in both 2D 14 and 3D 15 acquisitions. MRF‐derived T 1 and T 2 measurements are also repeatable over time, 16 with excellent reproducibility in vivo across different scanner types 17,18 . Several in vivo multicenter studies demonstrated high levels of repeatability and reproducibility of MRF in the brain 17,19 .…”
Section: Introductionmentioning
confidence: 92%
“…MRF-derived T 1 and T 2 measurements are also repeatable over time, 16 with excellent reproducibility in vivo across different scanner types. 17,18 Several in vivo multicenter studies demonstrated high levels of repeatability and reproducibility of MRF in the brain. 17,19 However, repeatability and reproducibility of the prostate MRF acquisition in phantom and prostatic tissues across different centers have not yet been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…The prostate MRF technique has been shown to have good intrascanner repeatability, although reproducibility across multiple different scanners has been shown to be slightly more variable but similar to other quantitative measures 9 . T1 and T2 values have also been shown to be reproducible with both 1.5 T and 3 T acquisition 99 . Continued assessment of reproducibility will enable creation of reliable normative quantitative data.…”
Section: Current Clinical Applicationsmentioning
confidence: 97%
“…9 T1 and T2 values have also been shown to be reproducible with both 1.5 T and 3 T acquisition. 99 Continued assessment of reproducibility will enable creation of reliable normative quantitative data.…”
Section: Prostate Imagingmentioning
confidence: 99%
“…However, the consistent results obtained from separate independent preliminary trials are encouraging. High inter-scanner reproducibility of MRF T1 relaxometry was reported for assessing healthy prostate recently for both 1.5T and 3T MRI scanners [ 66 ]. Similar studies in patients with suspected prostate cancer have yet to report their findings.…”
Section: Magnetic Resonance Fingerprinting For Imaging Cancermentioning
confidence: 99%